Methods of Blood Loss Quantification in Major Abdominal Surgery: A Narrative Review - Zajak, Ján; Páral, Jiří; Sirový, Miroslav; Odložilová, Šárka; Vinklerová, Kateřina; Balík, Michal; Čečka, Filip (Acta medica (Hradec Kralove), 2023)
Blood loss in major abdominal surgery is an essential parameter in the evaluation of strategies aimed at reducing perioperative bleeding. It is also an important parameter of quality of the surgical procedure, along with postoperative morbidity and mortality, radicality of the surgical resection, etc. However, blood loss quantification remains unreliable and inaccurate. The methods used to measure blood loss can be categorized as visual estimation, gravimetric method, direct measurement, spectrophotometry, calculation methods, colorimetric analysis, and miscellaneous. The aim of this work is to review up-to-date knowledge about the various methods of blood loss quantification and then to introduce study, which should compare more methods of blood loss quantification in a real surgical setting.
Keywords: Hemorrhage; krvácení; abdominal surgery; Humans; lidé; blood loss quantification